Factors Affecting Occupational Health of Shift Nurses: Focusing on Job Stress, Health Promotion Behavior, Resilience, and Sleep Disturbance - Da-Som Choi; Sang-Hee Kim (Elsevier, 2022)
Background: This study aims to allow the development of efficient measures to improve occupational health of shift-working nurses focusing on job stress, health promotion behavior, resilience, and sleep disturbance. Methods: It was conducted on a subject panel of 137 nurses who were aware of the purpose of the study and agreed to participate. They worked three shifts at a tertiary hospital or a general hospital located in metropolitan city B. The collected data were analyzed by the independent t test and one-way analysis of variance and post-tested by Scheffe's test, Pearson's correlation coefficients, and multiple linear regression analysis using SPSS/WIN 25.0. Results: The significant influencing factors on sleep disturbance were of those whose subjective health status was 'normal' (β = 0.29, p < .001), 'not healthy' (β = .40, p < .001), who have job stress (β = .22, p = .003), and who have health promotion behavior (β = -0.17, p = .023). The overall explanatory power was 31.1% (F = 16.31, p < .001). Conclusion: Through this study, nurses' subjective health status and job stress of working shifts were found to be important factors influencing the sleep disturbance level, and the most influencing factor was identified as the subjective health status.